2011
DOI: 10.1007/s10096-011-1248-4
|View full text |Cite
|
Sign up to set email alerts
|

Influenza-like illness in pregnant women during summertime: clinical, epidemiological and microbiological features

Abstract: It is not known whether influenza-like illnesses (ILI) in pregnant women caused by influenza virus, specifically, those caused by the 2009 Influenza A H1N1 virus (nH1N1), can be clinically distinguished from those caused by other agents. From 1st July 2009 until 20th September 2009, an observational study including all pregnant women presenting at Hospital Universitario La Paz with an ILI was carried out. A specific reverse-transcriptase polymerase chain reaction (RT-PCR) for nH1N1 in nasopharyngeal swabs was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
3
0
0
Order By: Relevance
“…These results showed that during the flu‐pandemic 2009–2010, non‐influenza respiratory viruses were recovered in 23% of pregnant women presenting with influenza syndrome while influenza A virus itself was detected in only 42% and oseltamivir prescribed in 88%. Interestingly, the diversity of viruses observed and their distribution were similar to those reported in a series of 45 pregnant women in Spain [Paño‐Pardo et al, ]. In addition, the comparison of these results with those of a British team [Gaunt et al, ] showed that the profile of respiratory viruses in pregnant women with influenza‐like illness was closer to the profile of viruses causing important disease burden in immunocompromised patients compared to non‐immunosuppressed adults.…”
Section: Discussionsupporting
confidence: 82%
“…These results showed that during the flu‐pandemic 2009–2010, non‐influenza respiratory viruses were recovered in 23% of pregnant women presenting with influenza syndrome while influenza A virus itself was detected in only 42% and oseltamivir prescribed in 88%. Interestingly, the diversity of viruses observed and their distribution were similar to those reported in a series of 45 pregnant women in Spain [Paño‐Pardo et al, ]. In addition, the comparison of these results with those of a British team [Gaunt et al, ] showed that the profile of respiratory viruses in pregnant women with influenza‐like illness was closer to the profile of viruses causing important disease burden in immunocompromised patients compared to non‐immunosuppressed adults.…”
Section: Discussionsupporting
confidence: 82%
“…The viral SARI rate among PW was higher than NPW, consistent with the findings from the state of Paraná. Influenza was the most frequent among the investigated viruses in PW, followed by hRV, in similar profile as described previously [5,14]. In accordance with to Azziz-Baumgartner et al (2021) [15], we did not identify any cases of hAdV among PW.…”
Section: Discussionsupporting
confidence: 92%
“…The influenza test was generally performed using specific PCR, but in five cases, multiplex PCR was performed, detecting two positive cases for rhinoviruses. Two retrospective studies conducted during the 2009–2010 flu pandemic found in pregnant women with influenza-like symptoms, non-influenza respiratory viruses rates of 23 %, and influenza H1N1 rates between 31 and 42 %, similar to our results [ 10 , 11 ]. The multiplex PCR was not used on a routine basis because it is expensive and time-consuming, although this strategy could possibly avoid use of antibiotics and hospitalizations.…”
Section: Discussionsupporting
confidence: 91%